TCF4 and COL8A2 Gene Polymorphism Screening in a Greek Population of Late-onset Fuchs Endothelial Corneal Dystrophy - Moschos,M.M.; Diamantopoulou, A.; Gouliopoulos,N.; Droutsas,K.; Bagli,E.; Chatzistefanou,K.; Kitsos,G.; Kroupis, C. (In Vivo, 2019)
BACKGROUND/AIM: Fuchs' endothelial corneal dystrophy (FECD) is a hereditary, progressive, bilateral, and irreversible disorder of the corneal endothelium. The purpose of this study was to develop a novel, accurate and high-throughput real-time polymerase chain reaction (PCR) method and melting-curve analysis in order to genotype the rs613872 polymorphism in the transcription factor 4 (TCF4) gene and to implement it on a well-ascertained sample of 22 Greek FECD patients and 58 healthy individuals, age- and sex-matched. PATIENTS AND METHODS: DNA was extracted from blood samples, which were screened with the DNA sequencing method in order to detect the g.31753T>G/p.L450W (rs8035192) and g.31767C>A/p.Q455K (rs8035191) mutations in a COL8A2 genomic region. RESULTS: TCF4 risk G allele frequency increased to 48% in FECD patients compared to 17% in healthy-subjects [OR=4.82 (95% CI=1.98-11.73)]. No p.L450W and p.Q455K COL8A2 gene mutations were detected. CONCLUSION: We confirmed that rs613872 in the TCF4 gene is strongly and statistically associated with late-onset FECD in a Greek population
Keywords: Aged; Aged,80 and over; Alleles; analysis; Blood; Collagen Type VIII; Diagnosis; Epidemiology; Female; Fuchs' Endothelial Dystrophy; Gene Frequency; Genetic Association Studies; Genetic Predisposition to Disease; genetics; Genotype; Greece; Humans; Male; Odds Ratio; Polymorphism,Genetic; Population Surveillance; Sequence Analysis,DNA; Transcription Factor 4